If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(n + -1) = 4(4f + -8) Reorder the terms: 3(-1 + n) = 4(4f + -8) (-1 * 3 + n * 3) = 4(4f + -8) (-3 + 3n) = 4(4f + -8) Reorder the terms: -3 + 3n = 4(-8 + 4f) -3 + 3n = (-8 * 4 + 4f * 4) -3 + 3n = (-32 + 16f) Solving -3 + 3n = -32 + 16f Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 3n = -32 + 3 + 16f Combine like terms: -3 + 3 = 0 0 + 3n = -32 + 3 + 16f 3n = -32 + 3 + 16f Combine like terms: -32 + 3 = -29 3n = -29 + 16f Divide each side by '3'. n = -9.666666667 + 5.333333333f Simplifying n = -9.666666667 + 5.333333333f
| x+y+6=12 | | 7z=48 | | -4z=14-5z | | -4z=14-5 | | (3x+7)=7x+15 | | -512=-8n+8(-8+8n) | | 5y^2-33y+18=0 | | -3-4x=1.5x-2 | | 6x+2=2x+5 | | -30=-3x | | 4.2x-0.88=1.68-2.2x | | 4x+2=-3x+4 | | a-9=132 | | 3*8-9=12-2*8 | | 5(3+3x)-5=85 | | P-15=54 | | 23x-7-17x+4=17x-4-11x+16 | | 13+3n=8n-3(n-4) | | 3x-9=12-2x | | -3(p+7)=21 | | 3(12w+4)= | | (3W^2-5W)-[(w^2+5w)-(4W^2-2w)]= | | -2(2f-4)=-4(-f+4) | | 18-(5m+3)=5+4m-17 | | 145-(6x+12)=6(x+7)+x | | 4p^2-21p-18=0 | | 5x+27=180 | | 3w^2-5w= | | 4x^2+6=330 | | x+1/2+2X+3x=55 | | 4x^2-42x+27=0 | | 3(9c-1)-18=25c+3 |